The ambiguity of dismissal of notary over bankruptcy in Indonesia - Rahayu Hartini (Faculty of Law, University of Muhammadiyah Malang, 2021)
A notary is a public official who has the authority to make authentic deeds and other authorities regulated in-laws and regulations. Notaries are also private legal subjects (natuurlijk persons), which have free will to carry out legal actions. According to the Law on Notarial Positions, a Notary is dishonorably dismissed when (s)he is declared bankrupt. On the other hand, the UUK and PKPU recognize the rehabilitation of bankrupt debtors if they have fulfilled their obligations. This is where there is ambiguity or a fuzzy norm (vegen norm). Legal research aims to find out how bankruptcy is regulated in the notary position, and what are the legal consequences for the position of a notary both as a person and in relation to his/her position as a notary public? This legal research is normative juridical using a statutory approach and a conceptual approach. The legal materials obtained are analyzed using content analysis. The results of the discussion: 1). Notary bankruptcy has been regulated in UUK and PKPU as well as in the Law on Notary Position. 2). The legal consequences for a Notary who is declared bankrupt by the Commercial Court have an impact on the notary's personality, as well as on his position. According to the Law on the Position of Notary Public, if violating Article 84 which results in losses to the parties, the notary is obliged to pay compensation. According to the UUK and PKPU, this could result in the debtor losing the right to act freely on his assets, but not losing the right to perform his/her tasks and hold a position. As a recommendation, in the Law on the Position of Notary Public, it is necessary to clearly define the separation of Notary as a person from her/his position as his profession.